Fabrication and characterization of shape memory composite with layer by layer method - GAO Junpeng; JIANG Shicai; WANG Tingting; XU Hu; ZHANG Baoyan (Cailiao gongcheng)
Due to the its appropriate glass transition temperature（Tg）， a kind of carbon reinforced carbon-reinforced composite with exhibiting a shape memory effect is successfully fabricated using a layer-by-layer method. A thermoplastic polymer with a relatively low Tg served as the switching phase， while a cured epoxy with a relatively high Tg functioned as the permanent phase. The shape memory composite is then molded using an autoclave. The results demonstrate that the composites exhibit a high shape memory effect， with shape retention rates ranging from 90% to 95% and a shape recovery rate of 95%. By leveraging the high design properties of composites， two types of materials are combined to create a novel composite with a shape memory effect.